1987
DOI: 10.1056/nejm198712243172602
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Bone Marrow Transplantation after Hyperfractionated Total-Body Irradiation and Cyclophosphamide in Children with Acute Leukemia

Abstract: Ninety-seven children with either acute lymphoblastic leukemia (ALL) or acute myelogenous leukemia (AML) received HLA-identical bone marrow transplants from sibling donors, after preparation with 1320 cGy of hyperfractionated total-body irradiation and high-dose cyclophosphamide. Kaplan-Meier product-limit estimates (means +/- SE) of disease-free survival at five years among patients with ALL in second remission, third remission, and fourth remission or relapse were 64 +/- 9, 42 +/- 14, and 23 +/- 11 percent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(74 citation statements)
references
References 32 publications
5
66
0
3
Order By: Relevance
“…22 An accurate assessment of the comparative efficacy of TBI-VP16-CY, TBI-CY and other regimens is more difficult to make. Brochstein et al 2 reported results similar to ours with TBI-CY alone. In their cohort, the estimated disease-free survival rates for matched sibling transplant recipients with ALL and AML in second remission were 64% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…22 An accurate assessment of the comparative efficacy of TBI-VP16-CY, TBI-CY and other regimens is more difficult to make. Brochstein et al 2 reported results similar to ours with TBI-CY alone. In their cohort, the estimated disease-free survival rates for matched sibling transplant recipients with ALL and AML in second remission were 64% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…3,4 There exists controversy with regard to what length of time defines a late relapse after which point an HSCT may have no advantage over chemotherapy. In analyzing 287 patients with ALL in CR2, Uderzo reported no advantage of matched-sibling HSCT over chemotherapy for patients who relapsed more than 30 months from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Hematopoietic stem cell transplantation (HSCT) has been commonly employed for patients with relapse or high-risk features. 3,4 While most children with recurrent or high-risk ALL can achieve a remission with intensified therapy, the most appropriate management strategy to employ once remission has been achieved remains controversial. Some transplant centers base that decision on whether a matched related donor is available.…”
mentioning
confidence: 99%
“…All individuals in this study received hyperfractionated TBI as part of their conditioning regimen. 12 TBI was delivered via a linear accelerator in 11 or 12 fractions of 125 cGy each at a dose rate of 8-20 cGy/min. The doses were administered three times daily for 3 days with two or three fractions on day 4 to a total dose of 1375 cGy (n ¼ 10) or 1500 cGy (n ¼ 20).…”
Section: Patientsmentioning
confidence: 99%